IMPLEMENTATION OF INDUSTRIAL WORK CULTURE IN VOCATIONAL HIGH SCHOOL - Gumilar, Gugum Surya; Wardaya, Wardaya; Sasmita, Asep Hadian (Journal of Mechanical Engineering Education, 2020)
At this time many companies are competing to provide education and cooperation with schools,especially the application of industrial work culture because there will be tax deduction incentivesone of the vocational high schools in Bandung has collaborated with industry and applied industrial work culture to learning.The absence of monitoring, controlling and evaluation on the part of the company and school makes the application of an industrial work culture unable to see the level of suitability and success. This problem encourages researchers to conduct research on the application of industrial work culture in vocational high schools in Bandung. This study aims to determine the suitability and results of the application of industrial work culture.Where the components applied to work culture are 5s, 3c, horenso and yoss check. The research method uses quantitative descriptive with data collection techniques in the form of industrial work culture questionnaires that have gone through expert validation and statistical validation. The results showed that industrial culture has a score of 87.30% interpretation criteria, which means that the application of industrial work culture is in accordance with the module, Then students have a self-control score for self-discipline of 75.75%, which means that the implementation of industrial work culture in schools is very good.